Splenogonadal Fusion Diagnosed by Doppler Ultrasonography - Jose Murillo B. Netto; Luis M. Pérez; David R. Kelly; David B. Joseph; Stuart A. Royal (The Scientific World Journal)
Splenogonadal fusion usually presents as a left scrotal mass but rarely is the diagnosis suspected preoperatively. Herein, we present the first report of a left splenogonadal fusion which was suspected preoperatively by doppler ultrasonography in a 2 year old boy.